Biology and Management of Graceful Sandmat (Chamaesyce hypericifolia) in Ornamental Crop Production - Theresa Chormanski; Chris Marble; Lyn Gettys (EDIS)
Graceful sandmat (Chamaesyce hypericifolia) is a problematic weed that often grows in container media in ornamental plant nurseries. This 4-page facts sheet profiles the biology of graceful sandmat and recommends physical, cultural, and chemicals methods for managing the weed in the nursery environment. Written by Theresa Chormanski, Chris Marble, and Lyn Gettys, and published by the UF Department of Environmental Horticulture, June 2015.